Konsep dan Pengarustamaan Gender dalam Pendidikan Islam - Sri Juwita; Ikbal Muhammad Wildan; Adang Hambali (Fakultas Agama Islam Universitas Billfath, 2023)
Writing articles aims to explain the concept and mainstreaming of gender in Islamic education. In the world of education, there is still a gender gap that needs to be overcome by strengthening and implementing gender equality. This research is a qualitative type, collecting data using literature studies by collecting data and taking ongoing discussions with research. The analytical method used is content analysis of content. The results of the study show that Islam highly values ​​gender equality which is reinforced in the explanation of the verses of the Koran. The Qur'an implies gender equality between men and women, namely that women and men have equality in terms of humanity, taklif, rewards, and rewards as well as opportunities for achievement. Gender mainstreaming in Islamic education can be carried out by implementing gender equality through curriculum correlation, incorporating gender-based issues into learning, using teaching materials that are not gender-biased, and providing opportunities for all students to participate in the learning process. The application of a gender mainstreaming strategy in Islamic education is very appropriate to be applied as an effort to reduce the level of discrimination and gender gaps in society.